Mazhab Tafsir Sufi: Sejarah, Metodologi, dan Tokoh-Tokoh Beserta Karyanya - Anugrah Pangestu; Syahla Ghaziyah; Ahmad Dasuki (JURNAL ILMIAH NUSANTARA, 2025)
Sufi exegesis is an approach to interpreting the Qur’an that emphasizes inner meanings and spiritual experiences in understanding divine revelation. This study aims to explore the historical development of Sufi exegesis, its methods and sources, as well as key figures and their works. Utilizing a literature review method, the research examines the contributions of Sufi exegetes such as Sahl al-Tustari, Al-Ghazali, Ibn Arabi, and Jalaluddin Rumi in developing interpretations that incorporate divinely inspired knowledge, inspiration, symbolic approaches, and mystical experiences. The findings indicate that Sufi exegesis plays a significant role in deepening the spiritual understanding of the Qur’an and promoting a moderate and inclusive Islamic perspective. Despite facing criticism for its subjective approach and lack of textual verifiability, Sufi exegesis remains relevant in the modern context, particularly in bridging religion and spirituality and encouraging a more tolerant and humanistic understanding of Islam.